Kinerja Pegawai dalam Menyukseskan Mini Market Pelayanan Publik - Fauzi, Rizky; Ikhbaluddin, I (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2020)
Minimarket Pelayanan Publik (Public Services Minimarket) is the next implementation of Pelayanan Administrasi Terpadu Kecamatan (Integrated Administration Services of Sub-district) (PATEN) as a government effort to provide convenient services to the community. Minimarket Pelayanan Publik as a public services innovation in Jekan Raya Sub-district. The purpose of the research is to find out the performance overview of the employee to succeed Minimarket Pelayanan Publik in Jekan Raya Sub-district. The assessment uses Moeheriono’s theory with the knowledge dimension about the job, work quality, employee, productivity, initiative, and responsibility. This research is qualitative research that used descriptive method and case study. Research result shows that employee performance of Jekan Raya Sub-district to succeed Minimarket Pelayan Publik has been included in a good category that can be seen from a lot of observation aspects and assessment of employee work daily and work pattern. However, we need to perfect some aspects.